Significant Enhancement of the Upconversion Emission in Highly Er3+‐Doped Nanoparticles at Cryogenic Temperatures. Issue 7 (10th January 2023) - Tu, Langping; Wu, Kefan; Luo, Yongshi; Wang, Enhui; Yuan, Jun; Zuo, Jing; Zhou, Ding; Li, Bin; Zhou, Jiajia; Jin, Dayong; Zhang, Hong
Abstract: Relatively low efficiency is the bottleneck for the application of lanthanide‐doped upconversion nanoparticles (UCNPs). The high‐level doping strategy realized in recent years has not improved the efficiency as much as expected. It is argued that cross relaxation (CR) is not detrimental to upconversion. Here we combine theoretical simulation and spectroscopy to elucidate the role of CR in upconversion process of Er 3+ highly doped (HD) UCNPs. It is found that if CR is purposively suppressed, upconversion efficiency can be significantly improved. Specifically, we demonstrate experimentally that inhibition of CR by introducing cryogenic environment (40 K) enhances upconversion emission by more than two orders of magnitude. This work not only elucidates the nature of CR and its non‐negligible adverse effects, but also provides a new perspective for improving upconversion efficiency. The result can be directly applied to cryogenic imaging and wide range temperature sensing. Abstract : By introducing a cryogenic environment to suppress the harmful cross relaxation, the upconversion intensity of Er 3+ ‐rich core–shell structures can be significantly improved over 100‐fold, together with an over 50‐fold modulation on the red‐to‐green emission ratio.